Population mapping and morphological variability of Eugenia involucrata (Myrtaceae, Myrteae) in Uruguay - Giagnacovo, Agustín; Pereira, José Luis; Trujillo, Cristina; Berberián, Natalia; Borges, Alejandra; Bonifacino, Mauricio; Speroni, Gabriela (Agrociencia Uruguay, 2025)
Eugenia involucrata DC. (Myrtaceae, Myrteae), cereza de monte, cerejeira, is a subtropical species that inhabits Argentina, Brazil, Bolivia, Paraguay, and Uruguay. However, Uruguayan collections are scarce, and floristic reports indicate that its occurrence is sporadic, and the species has been categorized as a priority for conservation due to its rarity. This species produces edible fleshy fruits with excellent organoleptic and nutraceutical properties, positioning it as a native fruit with high potential in regional fruit-growing programs. The objective of this study is to verify the presence of Eugenia involucrata in Uruguay and to evaluate the morphological variability within the species’ southernmost distribution area. The Cuareim river basin was explored, and flowering herbarium specimens and fruit samples from identified populations were collected for morphological analysis. Descriptive measurements were obtained, and multivariate statistical analyses were conducted for 7 leaf variables, 19 flower variables, and 7 fruit variables. The results indicate low interpopulation variability at the southern edge of its distribution, although some morphological characteristics and phenological data distinguish these populations from those in other areas. The identified populations show a promising scenario for reproductive success and gene flow in the area, while also representing a native phytogenetic resource with unique characteristics that could be valuable for incorporation into fruit production systems.